Demand response planning in capacity market using microgrid - Mohammad Khadem; Mahdi Karami (International Journal of Applied Power Engineering (IJAPE), 2022)
Planning of the demand response has received special attention due to the cost of transmission lines development and shortage of energy resources beside the growth of demand. This research work is focused on the role of microgrid (MG) as an alternative solution for transmission system development and proposed a method for modeling of MGs in the capacity market. The results show that using of MGs leads to reduce the development costs of transmission system. Moreover, MGs cause a slight increase in the profitability of selling capacity to the consumers. These outcomes prove that continuing to grow the number and capacity of MGs in each area ultimately eliminate the inquiry of transmission network development and minimize the cost of capacity market.